Drought tolerance selection of several tomato varieties by using polyethylene glycol - Sholeh Avivi; Novrida Yanti Sitompul; Tri Agus Siswoyo; Mohammad Ubaidillah (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
A prolonged dry season can cause drought stress and have an unfavorable impact on the growth of tomato plants, resulting in crop failure. Therefore, research is needed on the resistance of tomato varieties to drought stress. The recommended technique for drought resistance screening in tomatoes is in vitro cultivation using Polyethylene Glycol (PEG). The research aimed to obtain new varieties that could be used as promising lines for varieties tolerant to drought stress. The research method used included using ingredients in the form of 5 varieties of tomatoes (Ratna, Intan, Chung, Palupi, and Amelia) and 5 concentrations of PEG chemicals (0%, 5%, 10%, 15%, and 20%). Each seed of each tomato variety that had been sterilized using hypochlorite was germinated on MS0 media, then the germinated seeds with a size of ± 0.3 cm were transferred to MS0 + PEG treatment medium with each treatment concentration. The seeds that had been planted on the PEG-treated medium were then observed for growth for ± 4 weeks. The research data were analyzed using analysis of variance (ANOVA) and followed with DMRT at the 5% significance level. Based on the results, Palupi variety is the most tolerant variety, and Ratna variety is the most intolerant variety to drought stress. The higher the concentration of PEG used, the more it inhibits plant height, root length, and fresh weight of the roots.